The implementation of word splash strategy in teaching reading - Ragil Setiyawan; Rengganis Siwi Amumpuni (Universitas PGRI Madiun, 2018)
Reading is one of the basic skills which must be mastered by students especially in Junior High School. Word Splash is one of strategy in teaching reading. Word Splash is a strategy that is used to make prediction about the text that they will read. The purpose of the research are to describe the implementation of Word Splash strategy in teaching narrative reading, to describe the problems and to describe the solutions teaching narrative reading by using Word Splash Strategy. The researcher uses descriptive qualitative. The techniques of collecting data are observation, interview and documentation. The techniques of data analysis that used in this research are data condensation, data display and drawing conclusion and verification. The result of this research are: (1) The procedures of the implementation of Word Splash strategy are divided into three activities namely pre-activities, whilst-activities, post-activities. In pre-activities, the teacher gives greeting and check student attendance list. In whilst-activities, the teacher explains about the steps of Word Splash strategy. In post-activities, the teacher gives a review, conclusion and closing. (2) The problems of using Word Splash strategy are: the students difficult to make correct sentences. The students are confuse about the rule of Word Splash strategy. The students are difficult to understand when the teacher uses an unfamiliar narrative story. (3) The solution of the problems are: The teacher helps the students to make correct sentences. The teacher explains the strategy twice. The teacher uses a familiar narrative story. The teacher also suggested to improve their knowledge about various teaching strategy which is simple and efficient as like as using Word Splash strategy. The school is suggests to improve their teaching strategy which must not be expensive but it is interesting to be learned. Other researcher are suggests to take benefit of this research, so they can improve the quality of this research for other research in the different situation